Evaluation of Gross Hematuria and/or Drop in Hemoglobin in Post-Renal Biopsies within and after 8 Hours (Medical Forum Monthly, 2023)
Objective: To evaluate and optimize the observation time of post-biopsy complications to perform a percutaneous biopsy as a daycare procedure.Study Design: cross-sectional studyPlace and Duration of Study: This study was conducted at the department of Nephrology, The Kidney Centre Post Graduate Training Institute, Karachi, Pakistan from first August, 2020 till July, 2021.Materials and Methods: This cross-sectional study included 95 consecutive patients admitted to the hospital, which fulfilled our inclusion criteria for undergoing ultrasound-guided native renal biopsy. Relevant clinical and laboratory data were collected at admission, after eight hours and 24 hours post-biopsy. The data was entered and analyzed on IBM SPSS version 21. Shapiro Wilk's test checked the normality of dataResults: The mean age of our patients was 38.9±15 years, the youngest at 16 and the oldest at 77 years, with the female to male ratio of 1:1.2. Most biopsies were done due to renal dysfunction 44(46.3%), followed by nephrotic syndrome. Focal Segmental Glomerulosclerosis (FSGS) was the most common diagnosis in our patients 24(25.3%), followed by Acute Tubular Necrosis (ATN/ACN) 17 (17.9%) and diabetic nephropathy 12(12.6%).Conclusion: Elective native PRB is a safe procedure and can be done as a daycare procedure that reduces the overall cost of overnight hospitalization